Survei minat pelajar dalam mengikuti kegiatan ekstrakurikuler hockey - Septiadi, Catur; Maliki, Osa; Ratimiasih, Yulia (Edu Sportivo: Indonesian Journal of Physical Education, 2021)
The factors that influence student interest in participating in school-level hockey extracurricular activities are not yet known in Kebumen Regency. The purpose of this research is to see students' interest in participating in hockey extracurricular activities. The research method used is descriptive quantitative research using survey methods conducted through google form. The results showed that students' interest in participating in extracurricular hockey activities in Kebumen Regency from 12.36% of fun, 12.73% of attention, 12.46% of activities, 13.31% of motivation, 12.51% of teachers/trainers, facilities 11.95%, community 12.54%, and family 12.14%. The conclusion of this study is that students' interest in participating in extracurricular hockey activities in Kebumen Regency can be said to be more influenced by intrinsic factors (50.86%), while extrinsic factors (49.14%). From the results of this study, the advice that can be given is that the school should pay more attention to students who have high interest and motivation in extracurricular activities, especially hockey extracurricular activities and the improvement of facilities and infrastructure to support these extracurricular activities.